Integrating Literature in English Learning to Improve Multimodal Literacy through a Sociocognitive Approach - Imam Suhaimi; Futika Permatasari (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2024)
This study aims to explore the impact of literature integration in English language learning with a sociocognitive approach on the multimodal literacy skills of agricultural students. The research methods used include multimodal literacy tests before and after the intervention for 8 weeks, as well as a questionnaire to collect students' perceptions. Quantitative results showed that before the intervention, there was no significant difference in multimodal literacy skills between the experimental group (mean score 65.4) and the control group (mean score 64.8). However, after the intervention, the average score of the experimental group increased significantly to 85.2, while the control group only experienced a slight increase to 68.5. Inferential statistical analysis confirmed that the difference in score improvement between the two groups was significant (p <0.05), indicating the effectiveness of literature integration in improving multimodal literacy skills. Qualitative results from in-depth interviews with students revealed key themes related to the learning experience, including increased engagement and motivation, improved multimodal literacy skills, and better social interactions in the literature-based learning context. Students from the experimental group reported that literature helped them better understand cultural and historical contexts, improved critical thinking skills, and expanded their understanding of different modes of communication. These findings support the importance of using contextual and interactive learning strategies to enhance the effectiveness of English language learning in agricultural education contexts. This study makes an important contribution to curriculum development and teaching practices in higher education, considering the important role of multimodal literacy in modern education.